PENGARUH KEDISIPLINAN BELAJAR DAN BERPIKIR KRITIS TERHADAP KEMAMPUAN PENALARAN MATEMATIS - Shohwatul Islam Fadhilah; Ihwan Zulkarnain; Condro Endang Werdiningsih (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
The purpose of this study was to determine the effect of learning discipline and critical thinking on mathematical reasoning abilities. This research was conducted on eighth grade students of SMP Negeri 4 Tambun Selatan, Bekasi Regency with a random sampling technique. The data collection technique in this study was done by giving a questionnaire for the two independent variables and giving essay questions for the dependent variable. The research method used in this study is a survey with correlational techniques. The sample in this study was 68 students of class VIII. Based on the results of the study, it can be concluded that there is a significant relationship between learning discipline and critical thinking with mathematical reasoning abilities. This is indicated by Ftable = 3.14 and Fcount 8.57, so Fcount > Ftable (8.57 > 3.14). Thus, it can be concluded that learning discipline and critical thinking have an influence on mathematical reasoning abilities